Kajian Level Kadar Air dan Ukuran Partikel Bahan Pakan Terhadap Penampilan Fisik Wafer - Retno Iswarin Pujaningsih; Bambang Waluyo Hadi Eko Prasetiyono; Sri Mukodiningsih; Baginda Iskandar Moeda Tampoebolon; Cahya Setya Utama (Jurnal Agripet, 2013)
Study on the level of water content and particle size of feed ingredients to the physical appearance of waferABSTRACT. This study attempted wafer manufacturing technology development of conventional feed ingredients. The benefit of wafer increase feed consumption and feed efficiency, increase the metabolizable energy content of the feed, kill pathogenic bacteria, reduce the amount of feed scattered, extending the storage time, ensure the balance of feed nutrients and vitamins to prevent oxidation. Research was continuing several research activities on wafer manufacturing technology that has been done and continues to be developed by the researchers. The long term goal of a series of research is to obtain basic information to the wafer manufacturing optimum quality and measurable. Specific target is to obtain basic information about the quality of the wafer on the level of water content and the use of a certain particle size. The research method used was experimental and analytical methods in the laboratory. The results showed that based on the test of physical qualities (moisture content, density, water absorption) showed that the use of the level of moisture content up to 8% with a particle size of 10-20 mm feed material provides the best physical appearance of wafer.